PELUANG DAN TANTANGAN TRANSFORMASI DIGITAL DI INDONESIA - Wahidin, Darto; Ikmah Wati, Ikmah (Universitas Nusantara PGRI Kediri, 2024)
Digital transformation is a new fundamental change that refers to digital technology, which is increasingly developing rapidly. In this case, the digital transformation in Indonesia presents challenges and opportunities for the Indonesian people. The challenges and opportunities of digital transformation must be a top priority for the Indonesian government. This research aims to describe and examine in more depth the challenges and opportunities of digital transformation in Indonesia, as well as to find out the right strategy to face the challenges and opportunities of digital transformation. Furthermore, the method used in this research is qualitative, which refers to literature studies and previous research. In this research, there are data collection stages consisting of data reduction, data analysis, data presentation, and conclusion, as well as suggestions in this article. In this research, it can be concluded that the challenges and opportunities for transformation in Indonesia are quite large. These challenges and opportunities must be the main concern. Also, the right strategy is very influential in facing the challenges and opportunities of digital transformation in Indonesia.